Therapeutic evaluation of immunomodulators in reducing surgical wound infection. Issue 1 (14th December 2021) - Mahmud, Foyez; Roy, Ruchi; Mohamed, Mohamed F.; Aboonabi, Anahita; Moric, Mario; Ghoreishi, Kamran; Bayat, Mohammad; Kuzel, Timothy M.; Reiser, Jochen; Shafikhani, Sasha H.
Abstract: Despite many advances in infection control practices, including prophylactic antibiotics, surgical site infections (SSIs) remain a significant cause of morbidity, prolonged hospitalization, and death worldwide. Our innate immune system possesses a multitude of powerful antimicrobial strategies which make it highly effective in combating bacterial, fungal, and viral infections. However, pathogens use various stealth mechanisms to avoid the innate immune system, which in turn buy them time to colonize wounds and damage tissues at surgical sites. We hypothesized that immunomodulators that can jumpstart and activate innate immune responses at surgical sites, would likely reduce infection at surgical sites. We used three immunomodulators; fMLP (formyl‐Methionine‐Lysine‐Proline), CCL3 (MIP‐1α), and LPS (Lipopolysaccharide), based on their documented ability to elicit strong inflammatory responses; in a surgical wound infection model with Pseudomonas aeruginosa to evaluate our hypothesis. Our data indicate that one‐time topical treatment with these immunomodulators at low doses significantly increased proinflammatory responses in infected and uninfected surgical wounds and were as effective, (or even better), than a potent prophylactic antibiotic (Tobramycin) in reducing P . aeruginosa infection in wounds. Our data further show that immunomodulators did not have adverse effects on tissue repair and wound healing processes. Rather, they enhanced healing in both infected and uninfected wounds. Collectively, our data demonstrate that harnessing the power of the innate immune system by immunomodulators can significantly boost infection control and potentially stimulate healing. We propose that topical treatment with these immunomodulators at the time of surgery may have therapeutic potential in combating SSI, alone or in combination with prophylactic antibiotics.